2009
DOI: 10.1097/hco.0b013e328324e679
|View full text |Cite
|
Sign up to set email alerts
|

International normalized ratio patient self-management for mechanical valves: is it safe enough?

Abstract: The concept of INR self-management is a promising tool to achieve low hemorrhagic complications without increasing the risk of thromboembolic complications. Data of the Early Self-Controlled Anticoagulation Trial (ESCAT II) study demonstrate that low-dose INR self-management does not increase the risk of thromboembolic events compared with conventional-dose INR self-management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
7
1
1
Order By: Relevance
“…11,13 Six different centers across Germany participated in the ESCAT II study. 11,12 We included only patients from the Bad Oeynhausen center (881 patients) because this was the only center that had collected the detailed patient and perioperative information that we needed for our study. During patient selection for the propensity score analysis, we did not make a distinction between the 2 groups in the ESCAT II trial because there were no differences between the groups that were relevant for this study.…”
Section: Source Of Study Datamentioning
confidence: 99%
See 1 more Smart Citation
“…11,13 Six different centers across Germany participated in the ESCAT II study. 11,12 We included only patients from the Bad Oeynhausen center (881 patients) because this was the only center that had collected the detailed patient and perioperative information that we needed for our study. During patient selection for the propensity score analysis, we did not make a distinction between the 2 groups in the ESCAT II trial because there were no differences between the groups that were relevant for this study.…”
Section: Source Of Study Datamentioning
confidence: 99%
“…11,12 The German-Dutch Ross Registry is a prospective multicenter cohort study with 1742 patients. Started in February 1991, the registry includes data from 12 cardiothoracic surgery departments in the Netherlands and Germany [7][8][9][10] (see the online-only Data Supplement for a list of participating centers).…”
Section: Source Of Study Datamentioning
confidence: 99%
“…Перспективным является обучение пациентов методам самотестирования и самоконтроля МНО с помощью портативных аппаратов [10,11], ис-пользование которых повышает приверженность к лечению и уменьшает частоту возникновения геморрагических и тромботических осложнений [12][13][14][15][16] в результате стабилизации целевого диа-пазона МНО [17,18].…”
Section: централизованная система контроля мноunclassified
“…We also searched for conference article (from ISI Web of Knowledge Platform of ISI Proceedings), unpublished degree dissertation (from ProQuest Digital Dissertations). Furthermore, relevant trials were identified through a manual search of secondary sources including references of initially identified articles and recent review articles [28]. Finally, a review of ClinicalTrials.gov was conducted to identify trials that may be eligible for inclusion.…”
Section: Search Strategymentioning
confidence: 99%